Synthesis and characterization novel magnetic nanoparticle (MNPS) metal based catalyst for carbon dioxide treatment in flue gases power plant - Halim, Ahmad Zamani Abdul (2019)
The increase of carbon dioxide (CO2) emission from coal-fired plants into the atmosphere has resulted in global warming and caused disastrous environmental pollution. The utilization of CO2, as a renewable carbon source to produce value-added chemicals, has attracted much interest for application of promising alternative technologies. The CO2 catalytic methanation is one of the attractive ways to approach the environmentally friendly synthesis of sustainable chemical feedstocks. This study is aimed to synthesize and study the applicability of copper (Cu) and manganese (Mn) over ruthenium-magnetic nanoparticle catalyst (Ru-MNPs) for conversion of CO2 into methane (CH4). The catalysts were prepared by wet impregnation (WI) method with different percentage of Cu or Mn incorporated and undergo calcination at 400°C, 700°C and 900°C. The selected catalyst was characterized with instruments of X-ray diffraction (XRD), Fourier transform infra-red (FTIR), Brunauer, Emmett and Teller (BET) and Scanning electron microscopy (SEM). The results showed concluded that 1.0Ru/80Cu-MNPs catalyst calcined at 900oC showed the highest catalytic activity, with 93.4% CO2 conversion at 250oC reaction temperature. The second active catalyst was 1.0Ru/80Mn-MNPs with 90.1% CO2 conversion at 250oC reaction temperature. From the characterization, the XRD result for Cu based catalyst showed that the active species were RuO2, Fe3O4 and CuO, while SEM assigned the presence of small particles that homogeneously distributed. For Mn based catalyst the active species were RuO2, Mn3O4 and Fe3O4 with small particles that homogeneously distributed as in SEM analysis. Higher surface area and a macrospore obtained from BET analysis might contribute to a higher catalytic activity. Furthermore, mechanistic study by FTIR showed Cu based catalyst was proposed tended to form monodentate carbonate at the initial state before forming the formate species when it was hydrogenated and finally releasing the methane.